Islam - Amer, Fatma (Laguna Hills, CA QEB Publishing, Inc., 2006)
Followers of Islam are called Muslims and their religion is based on the teachings of the Qur'an, its sacred book. The word Islam means "peace" and "submission." Muslims believe that their prophet,, Muhammad, was visited by an angel who revealed Allah's words.
5 - 9
Keywords: Muslims; Religions; World of Faiths